2017
DOI: 10.1259/bjr.20170473
|View full text |Cite
|
Sign up to set email alerts
|

The future of interventional and neurointerventional radiology: learning lessons from the past

Abstract: The rapid progression of medical imaging technology and the ability to leverage knowledge from non-invasive imaging means that Interventional Radiologists (IRs) and Interventional Neuroradiologists are optimally placed to incorporate minimally invasive interventional paradigms into clinical management to advance patient care. There is ample opportunity to radically change the management options for patients with a variety of diseases through the use of minimally invasive interventional procedures. However, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 50 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…4 Although most countries officially define the workday as eight hours, many doctors experience working hours well-beyond nine hours due to the need of 24-hour patient-care coverage. 5,6 Neurointerventionists and the rest of the stroke management team are currently feeling the effects of the changes in acute ischemic stroke (AIS) management, 7 due in part to the mounting level of evidence from several large randomized controlled studies since 2015 that demonstrated the value of endovascular therapy (EVT) for first-line and delayed treatment. [8][9][10][11][12][13][14][15][16][17] The significant increase in the number of EVT-eligible patients has proportionally increased the emergency caseload for the neurointerventionists as well as the whole support staff in the stroke unit which extends the number of hours at work and could be a potential source of fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although most countries officially define the workday as eight hours, many doctors experience working hours well-beyond nine hours due to the need of 24-hour patient-care coverage. 5,6 Neurointerventionists and the rest of the stroke management team are currently feeling the effects of the changes in acute ischemic stroke (AIS) management, 7 due in part to the mounting level of evidence from several large randomized controlled studies since 2015 that demonstrated the value of endovascular therapy (EVT) for first-line and delayed treatment. [8][9][10][11][12][13][14][15][16][17] The significant increase in the number of EVT-eligible patients has proportionally increased the emergency caseload for the neurointerventionists as well as the whole support staff in the stroke unit which extends the number of hours at work and could be a potential source of fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to surgery, IR training via simulation, allows for skills to be practiced and evaluated in a controlled environment by identifying strengths and weaknesses. Previous reports suggest that incorporating IR simulation in undergraduates greatly enhances the skill-set of students planning to follow a career in IR as well as those pursuing allied interventional specialties such as cardiology, anaesthetics and intensive care (Maingard et al 2017). In fact, up to 19% of newly qualified juniors end up in interventional specialities (The Royal College of Radiologists 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, a minority of IRs had Facebook accounts, and whilst this may not include all accounts with high privacy settings, this may reflect a lost opportunity for IRs in Australia. As IRs become more engaged with active patient management, including the increasing frequency of interventional radiology clinic appointments, the requirement for self‐promotion in the private practice setting may continue to increase and be a driver of future social media use 34 …”
Section: Discussionmentioning
confidence: 99%